2012
DOI: 10.2527/jas.2012-5477
|View full text |Cite
|
Sign up to set email alerts
|

National Beef Quality Audit-2011: Harvest-floor assessments of targeted characteristics that affect quality and value of cattle, carcasses, and byproducts1, 2

Abstract: The National Beef Quality Audit-2011 (NBQA-2011) was conducted to assess targeted characteristics on the harvest floor that affect the quality and value of cattle, carcasses, and byproducts. Survey teams evaluated approximately 18,000 cattle/carcasses between May and November 2011 in 8 beef processing facilities. Cattle identification methods were lot visual tags (85.7%), individual visual tags (50.6%), electronic tags (20.1%), metal-clip tags (15.7%), other (5.3%), none (2.5%), and wattles (0.5%). Hide colors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 24 publications
(38 reference statements)
1
42
2
1
Order By: Relevance
“…White and Renter (2009) concluded that the use of lung lesions as a diagnostic tool for bovine respiratory disease complex (BRDC) was far superior to that of a traditional clinical illness evaluation. Prevalence rates for liver abscesses (a sequela to ruminal acidosis) in surveys of U.S. fed cattle are different than the diagnosis rates for digestive diseases reported by the USDA (4.3%; USDA, 2011) versus 13.9 (Garcia et al, 2008) and 4.8% (McKeith et al, 2012). Multiple reports have outlined the deleterious effects on performance and carcass characteristics of liver abscesses (Brink et al, 1990;Nagaraja and Chengappa, 1998;Brown and Lawrence, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…White and Renter (2009) concluded that the use of lung lesions as a diagnostic tool for bovine respiratory disease complex (BRDC) was far superior to that of a traditional clinical illness evaluation. Prevalence rates for liver abscesses (a sequela to ruminal acidosis) in surveys of U.S. fed cattle are different than the diagnosis rates for digestive diseases reported by the USDA (4.3%; USDA, 2011) versus 13.9 (Garcia et al, 2008) and 4.8% (McKeith et al, 2012). Multiple reports have outlined the deleterious effects on performance and carcass characteristics of liver abscesses (Brink et al, 1990;Nagaraja and Chengappa, 1998;Brown and Lawrence, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…According to the National Beef Quality Audit (NBQA) 2000 (McKenna et al, 2002), NBQA-2005(Garcia et al, 2008, and NBQA-2011(McKeith et al, 2012 approximately 6.0% of harvested cattle were of the Holstein phenotype, which is equal to nearly 2 million Holstein cattle being harvested in 2012. Thus, Holstein cattle have become an integral component of the U.S. fed cattle market.…”
Section: Introductionmentioning
confidence: 99%
“…According to the most recent National Beef Quality Audit Report, 20.9% of livers were condemned at slaughter, and liver abscesses accounted for approximately two-thirds of liver condemnations (McKeith et al, 2012). Feeding of high-grain-based finishing diets may result in Liver abscesses in cattle: A review of incidence in Holsteins and of bacteriology and vaccine approaches to control in feedlot cattle 1,2…”
Section: Introductionmentioning
confidence: 99%